Coinfection of Influenza Virus and Group A Streptococcus in an Adult Suspected with Infectious Mononucleosis by Epstein-Barr Virus Infection - Masafumi Seki; Nozomi Oikawa; Maya Hariu; Yuji Watanabe (Global Journal of Clinical Virology - Peertechz Publications, 2016)
The patient was a 21 year-old male who showed high fever and an influenza virus B antigen positive nasal specimen. He was initially suspected as influenza-related bronchitis and pharyngitis by group A Streptococcus; however, his fever, sore throat and skin eruption did not improve although he was administered anti-influenza drugs and amoxicillin for four days. He was admitted to our hospital and underwent microbial and serological examinations. Serology indicated recent Epstein-Barr infections. His symptoms and fever declined during drug free observation. He was finally diagnosed as having a Epstein- Barr virus infection followed by coinfection of influenza B and group A Streptococcus with penicillin allergy, which may be relatively common in adults, and should be kept in mind.